Exploring three sides of whistleblowing - Yokhebed Widhianingtyas; Aprina Nugrahesthy Sulistya Hapsari (Universitas Muhammadiyah Yogyakarta, Indonesia, 2023)
Research aims: The research was conducted at the Faculty Student Senate of Information Technology, Faculty Student Senate of Economics and Business, and Faculty Student Senate of Social and Communication Sciences at ABC University to explore three sides of whistleblowing, i.e., motives, reporting channels, and reporting media that can be used as a means of mitigating fraud in the management of student funds.Design/Methodology/Approach: This qualitative descriptive study used the primary data obtained through a questionnaire fill-out as an initial survey and further deepened through semi-structured interviews with the respondents. Some respondents involved were the treasurers of faculty, heads of SMF, and treasurers of SMF.Research findings: The results indicate that the intention of SMF functionaries to carry out whistleblowing aligns with the theory of reasoned action. Furthermore, the motives that underlie the whistleblowing intentions from external factors comprise organizational justice, the application of ethics in the work environment, and the whistleblower’s position in the organization. Meanwhile, the motives for internal factors include trust in the leadership, professional commitment, and confidence in the evidence of fraud. Anonymous reporting is also preferred for whistleblowing. Thus, as a reporting media, the university should provide an integrated whistleblowing system.Theoretical contribution/Originality: This research is expected to be useful for the functionaries of the Faculty Student Senate at ABC University by providing knowledge and means of evaluating various motives and reporting channels that can encourage them to carry out whistleblowing as an effort to mitigate fraud. In addition, this research is anticipated to be used by ABC University to evaluate the policy of designing a whistleblowing mechanism and providing reporting media options that can be used. Theoretically, this research is hoped to be additional literature related to developing the whistleblowing concept in terms of motives, reporting channels, and reporting media on fund management fraud in student organizations.